Monitoring and assessing of changes in soil and groundwater salinity of Yemisli Irrigation District of Turkey using low quality irrigation water (International Journal of Irrigation and Water Management, 2019)
Low irrigation efficiency, high saline irrigation water, heavy soil texture, lack of adequate field drainage systems may cause soil salinity and drainage problems in irrigated agriculture. The mentioned problems are major treats for the sustainability of irrigated agriculture. This study carried out in 2007 was undertaken in 7,110 ha of area under the directive of Yemisli Irrigation Association (YIA) in Lower Seyhan Plain, on Southern coastal plains in Turkey. Growers in the area use low quality irrigation return flows of up-stream areas for irrigation. Irrigation method commonly used in the region is flood irrigation with low field irrigation efficiency. This work examines if using low quality of irrigation water causes drainage and soil salinity problem. For this purpose, a year around survey of 55 groundwater observation wells was carried out. Groundwater depths in the observation wells in February, March, June, July and October were measured. Salinity of the water samples collected from the wells was measured as electrical conductivity (ECw at 25°C). Additionally, soil samples from 0 to 30, 30 to 60 and 60 to 90 cm depths at 34 randomly selected sites were analyzed for soil salinity (ECe at 25°C) and alkalinity (SAR). The mean groundwater depth was the minimum (0.97±0.29 m) in March, before starting of the irrigation season. In October, following completion of the irrigation season, the groundwater depth was the highest (1.59 ± 0.13 m). Groundwater EC, greater than 20 dS m-1 , was noted commonly. In 93% of the study area, ECw was higher than 5 dS m-1 . Mean soil salinity ECe was higher below 1 m depth compared with that of surface layers. Likely occurrence of soil alkalinity (that is, sodium effect) was greater in sub-soil below 30 cm depth compared with surface layers. The results of the study showed that the soils of the area may become salt or even sodium affected in the future unless the present practice of irrigation management is changed.